PENGARUH MEDIA VIDEO STORY TELLING BERBASIS ANIMASI TERHADAP HASIL BELAJAR SISWA MATERI TEKS ARGUMENTASI KELAS IV SDN KEPUH KIRIMAN 1 WARU - Sinatrya, Indar; Sulistyawati , Ida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Technological advancements necessitate that educators maximize the utilization of technology in the classroom, which is driving this research. A well-planned educational experience is essential, and one way to ensure that students learn is to cultivate an engaging environment that piques their interest in the subject matter. Teachers may create a welcoming classroom environment by utilizing animated narrative video media. Finding out how SDN Kepuh Kuncian 1 Waru's fourth graders learn argumentative text through the use of animation-based video story telling media is the primary goal of this research. This study used a post-test only control group design, a quasi-experimental research style. In this study, fourth graders were split into two groups: one that utilized traditional teaching techniques and another that used animation-based video story telling medium. Observation and post-tests administered following therapy were utilized to gather data. We anticipate that the study's findings will shed light on how well animation-based video story telling works as a medium for enhancing students' learning outcomes and offer suggestions on how to best use interactive learning materials into classroom instruction. Keywords: Video Media, Animation Based Story Telling, Learning Outcomes